Pembentukan Rumus Sederhana Pendugaan Bobot Hidup Sapi Persilangan Simental dengan PO Berdasarkan Ukuran Tubuh - Yurnalis Yurnalis (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
The objective of the research was to find out the simple model of regression equation for estimation of body weight (y in kg) based on the data of other body parameters of Simmental and Ongole Cross cattle's. Sixty two bulls and thirty six cow kept by farmer in Padang Panjang, West Sumatra were measured their body of body length (x1 in cm), thorax circle (x2 in cm), shoulder high (x3 in cm). Criteria for choosing the best equation are R2, R2 Adjusted, Mean square Error (MSE). Thirty equation was considered for choosing the best equation. The best equation for predicting of body weight of bulls were y = 0,018(x2 -18)'2 and y = 0,000124(x1'2 * x2), while .for cows: y = 0,0156(x2 - 6)'2 and y = 0,000118(x1'2 * x2).